1997
DOI: 10.1002/(sici)1097-0029(19971215)39:6<506::aid-jemt5>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of insect mechanoreceptors

Abstract: This paper reviews the structure and function of insect mechanoreceptors with respect to their cellular, subcellular, and cuticular organization. Four types are described and their function is discussed: 1, the bristles; 2, the trichobothria; 3, the campaniform sensilla; and 4, the scolopidia. Usually, bristles respond to touch, trichobothria to air currents and sound, campaniform sensilla to deformation of the cuticle, and scolopidia to stretch. Mechanoreceptors are composed of four cells: a bipolar sensory n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
314
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 390 publications
(325 citation statements)
references
References 148 publications
(199 reference statements)
10
314
1
Order By: Relevance
“…From their distal tip, wild-type sensory neurons contain a sensory cilium (outer segment), followed by a connecting cilium and two basal bodies (centrioles). These basal bodies exist at the distal end of the dendrite (inner segment) (Keil 1997). Within the specialized mechanosensory cilium, a rich array of tightly packed microtubules (tubular body) is surrounded by the plasma membrane and delimited by the dendritic sheath ( Figure 1I).…”
Section: Meca Mutant Flies Have No Mechanoreceptor Currentmentioning
confidence: 99%
See 3 more Smart Citations
“…From their distal tip, wild-type sensory neurons contain a sensory cilium (outer segment), followed by a connecting cilium and two basal bodies (centrioles). These basal bodies exist at the distal end of the dendrite (inner segment) (Keil 1997). Within the specialized mechanosensory cilium, a rich array of tightly packed microtubules (tubular body) is surrounded by the plasma membrane and delimited by the dendritic sheath ( Figure 1I).…”
Section: Meca Mutant Flies Have No Mechanoreceptor Currentmentioning
confidence: 99%
“…The dendrite of many of these neurons is composed of two parts: the inner segment and the sensory cilium (Keil 1997;Swaroop et al 2010) ( Figure 1A). The sensory cilium is composed of a connecting cilium, which is a specialized ciliary transition zone (Malicki and Avidor-Reiss 2014), and an outer segment, which houses the sensory transduction machinery .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thurm (1964) showed that the cuticle at the base of each sensillum of the honey bee hair plate is elastic and stains positively with methylene blue, one of Weis-Fogh's (1960) diagnostic characteristics for identification of resilin. Subsequently, transmission electron microscopy has shown that the flexible socket cuticle, termed the joint membrane, is composed of a homogeneous material, possibly resilin (Matsumoto and Farley, 1978;Keil and Steinbrecht, 1984;Keil, 1997), embedded in a matrix of fibrous cuticle. Touch sensilla are likely to undergo many repeated deflections in an insect's lifetime.…”
Section: Resilin Expression In Developing Touch Receptorsmentioning
confidence: 99%